Microwave characterization of zinc/aluminium and magnesium/aluminium layered double hydroxides filled with polyvinyl chloride composites - Salih, Ethar Yahya (2014)
In recent years, many conventional plastic materials filled with materials have been proposed as alternatives to the most expensive mu-metal for electromagnetic interference applications. Some of these new materials claimed to have shielding effectiveness (SE) values as high as 130 dB. However it would be unnecessarily expensive in many applications if the objective is only to block the interference signals when even a 1dB SE is sufficiently enough. Shielding can also be improved by increasing the material thickness. This thesis presents an extensive investigation of the properties of Zinc/Aluminium (ZLDH) and Magnesium/Aluminium (MLDH) Layered double hydroxide (LDHs) filled with Polyvinyl Chloride (PVC) composites as new shielding materials for microwave applications. The ZLDH and MLDH were prepared using the co-precipitation method, while the PVC-ZLDH/MLDH composites were prepared in Tetrahydrofuran (THF) solvent. The d-spacing obtained from the XRD analysis were 8.95 and 8.13 Å for ZLDH and MLDH, respectively. The EDX analysis results indicate that all elements are traceable. The samples were placed in closed T/R rectangular waveguide. The dielectric properties of the PVC-ZLDH/MLDH composites were measured in the frequency range from 1 MHz to 1.2 GHz using the capacitance technique with an impedance analyser. The dielectric properties were also determined using closed T/R rectangular waveguide technique with a vector network analyser in the X-band frequency range (8-12 GHZ) from the measured transmission and reflection coefficients (|S11|, |S21|). The higher percentage of the fillers the higher were the magnitude of the |S11| and the lower were the magnitude of |S21|. The shielding effectiveness of PVC can be increased from 1.06 dB to 2.5 dB for 1 mm sample thickness by adding 7% and 5% of ZLDH and MLDH, respectively. The results of the dielectric properties demonstrated a noteworthy increase in both dielectric constant and loss factor of the PVC after introducing the fillers. It was found that adding 5% of the fillers changed the property of PVC from medium loss to high loss material. Theoretically, the calculation of magnitudes |S11| and |S21| were carried out using Finite Element Method (FEM), Finite Integral Technique (FIT) and Nicholson-Rose-Weir technique (NRW); the results were compared with the measured |S11| and |S21|. The results of the relative error of |S11| and |S21| suggest the FEM is the most accurate method. The mean relative errors of FEM were 0.158 and 0.045 for |S11| and |S21|, respectively. In contrast, the respective mean relative errors of FIT were 0.20 and 0.069 whilst the NRW were 0.183 and 0.087.